Corticosteroid Use and Growth After Pediatric Solid Organ Transplantation: A Systematic Review and Meta-Analysis. Issue 4 (April 2017) - Tsampalieros, Anne; Knoll, Greg A.; Molnar, Amber O.; Fergusson, Nicholas; Fergusson, Dean A.
Abstract : Background: A number of corticosteroid minimization and avoidance protocols for post–solid organ transplant have been developed. The study objective was to examine the effect of corticosteroid withdrawal/avoidance on growth and safety parameters in pediatric solid organ transplant recipients. Methods: A systematic review using Medline and Embase was performed. All randomized controlled trials (RCT) and observational studies comparing corticosteroid withdrawal/avoidance to controls receiving corticosteroids in pediatric transplant recipients which reported growth as change in height or final height were included. Two reviewers independently abstracted study data and assessed quality. Results: The search yielded 930 records, 14 separate studies involving 1146 patients. Renal RCTs (n = 5) showed that corticosteroid withdrawal/avoidance was associated with a significant increase in growth (mean difference in height standard deviation score [SDS], 0.18; 95% confidence interval [95% CI], 0.07-0.29; P = 0.001) compared with those remaining on steroids. In liver RCTs (n = 2), mean difference in height SDS was −0.20 (95% CI, −1.08 to 0.68; P = 0.66). Results for renal observational studies (n = 5) was 0.34 (95% CI, 0.03-0.65; P = 0.03). The most pronounced effect was seen in prepubertal children with SDS of 0.28 (95% CI, 0.14-0.41; P < 0.0001). In pubertal participants this was not observed (SDS, 0.06; 95% CI, −0.04 to 0.15; P = 0.24). Corticosteroid withdrawal/avoidance was not associated with acute rejection (odds ratio [OR], 0.87; P = 0.63), graft failure (OR, 0.45; P = 0.08), or death (OR, 0.34; P = 0.16) in renal trials. Conclusions: Corticosteroid withdrawal/avoidance in pediatric renal transplantation is associated with a significant improvement in height. Prepubertal patients appeared to have the greatest benefit. Importantly, the improvement in growth was not accompanied by increased rejection or worsening patient/allograft survival in the short term. Abstract : Corticosteroid withdrawal/avoidance in pediatric renal transplantation, especially in prepubertal patients is associated with a significant improvement in height without any adverse events, including increased rejection or worsening patient/allograft survival in the short term.